Rethinking corporal punishment in Malaysian schools: a legal discourse with lessons from Sweden - Fionne Teo Swee Yee; Nadhilah A.Kadir (Penerbit Universiti Kebangsaan Malaysia, 2025)
Corporal punishment has long been a common disciplinary measure in Malaysian schools, supported by both school authorities and parents. However, with increasing global emphasis on children's rights, the Convention on the Rights of the Child (CRC) classifies corporal punishment as degrading treatment. Despite Malaysia's ratification of the CRC, the practice remains permissible due to a reservation to Article 37, leading to incidents of harm and ongoing debates about its appropriateness. This study examines Malaysia’s legal frameworks regarding corporal punishment and their compliance with the CRC. A comparative analysis with Sweden, which has successfully banned corporal punishment, highlights the effectiveness of educational initiatives in fostering positive social change. Malaysia’s approach, which limits corporal punishment to mild measures, contrasts with Sweden’s reliance on public education to promote non violent and positive discipline. This study further identifies challenges in banning corporal punishment in Malaysia, including cultural beliefs and disciplinary concerns, and proposes gradual steps toward prohibition The study employs qualitative research methods, drawing from primary sources such as such as Malaysian legislation and policies, and secondary sources like academic literature. While Malaysia is not yet ready to fully abolish corporal punishment, a multi-faceted approach focusing on legislative reforms and public awareness can pave the way for a more child-friendly disciplinary environment.